Balo's concentric sclerosis: a clinical case - I. V. Litvinenko; G. N. Bisaga; V. S. Chirsky; R. F. Gimadutdinov; P. S. Dynin; S. Yu. Golokhvastov; V. Yu. Lobzin (Неврология, нейропсихиатрия, психосоматика)
This paper describes a case of Balo's concentric sclerosis, a rare demyelinating disease of the central nervous system (CNS), which is currently classified as multiple sclerosis. In recent years, there has been a more favorable clinical course of Balo's sclerosis. The significant polymorphism of clinical manifestations of the disease, its neuroimaging pattern, and laboratory tests cause difficulties diagnosing this pathology. Its differentiation with CNS tumors presents a particular challenge. So it also happens in the described clinical case, when computed tomography revealed the signs of space-occupying lesion, the histological pattern of concentric focus biopsy specimen indicated the presence of protoplasmic astrocytoma. However, immunohistochemical analyses of the biopsy specimen, immunological examination of cerebrospinal fluid, as well as the typical magnetic resonance imaging changes of Balo's sclerosis could suggest the demyelinating nature of the pathological process. The article shows that immunohistochemical techniques for examining a brain biopsy specimen and immunological assays of blood and cerebrospinal fluid are of great diagnostic value.